Supported decision-making to assist older persons experiencing elder abuse: An integrative review. Issue 4 (August 2021) - Strickland, Karen; Bail, Kasia; Cope, Sarah; Turner, Murray; Moss, Cameron
Abstract: Background: Elder abuse is an ongoing issue experienced by older persons in Australia, with instances of neglect, emotional, and physical abuse being reported to the Royal Commission into Aged Care Quality and Safety. Aim: The aim of this integrative review was to explore the evidence on the effectiveness of supported decision-making for applying to advocacy in older people and people experiencing elder abuse. Methods: A systematic search was conducted in accordance with the Preferred Reporting Items for Systematic Review and Meta-analyses guidelines, across multiple databases including: MEDLINE, CINAHL, PsycInfo, Cochrane Library, Web of Science, Scopus, and Trove. One thousand two hundred-ten articles were screened for relevance using titles and abstracts. Of these, seven met the inclusion criteria. Findings: Content analysis informed the development of four themes pertaining to supported decision-making amongst older persons: personal and environmental factors, relationship between decision maker and support person, information and training, and models and frameworks to aid assessment. Discussion: Supported decision making presents an important move towards promoting, protecting, and ensuring human rights for people who may have previously been exposed to more paternalistic approaches. Conclusion: The review highlighted gaps in the strength of evidence and was therefore not able to offer conclusive advice on of effectiveness of supported decision making in older people experiencing abuse. This review highlights the need for further research to be conducted to identify how best to offer supported decision making to support the autonomy and human rights of the older person.